THP-1 Macrophages and SGBS Adipocytes – A New Human in vitro Model System of Inflamed Adipose Tissue - Keuper, Michaela; Dzyakanchuk, Anna; Amrein, Kurt E.; Wabitsch, Martin; Fischer-Posovszky, Pamela (Frontiers in Endocrinology, 2011)
Obesity is associated with an accumulation of macrophages in adipose tissue. This inflammation of adipose tissue is a key event in the pathogenesis of several obesity-related disorders, particularly insulin resistance. Here, we summarized existing model systems that mimic the situation of inflamed adipose tissue in vitro, most of them being murine. Importantly, we introduce our newly established human model system which combines the THP-1 monocytic cell line and the preadipocyte cell strain SGBS. THP-1 cells, which originate from an acute monocytic leukemia, differentiate easily into macrophages in vitro. The human preadipocyte cell strain SGBS (Simpson-Golabi-Behmel syndrome) was recently introduced as a unique to tool to study human fat cell functions. SGBS cells are characterized by a high capacity for adipogenic differentiation. SGBS adipocytes are capable of fat cell-specific metabolic functions such as insulin-stimulated glucose uptake, insulin-stimulated de novo lipogenesis and beta-adrenergic-stimulated lipolysis and they secrete typical adipokines including leptin, adiponectin, and RBP4. Applying either macrophage-conditioned medium or a direct co-culture of macrophages and fat cells, our model system can be used to distinguish between paracrine and cell-contact dependent effects. In conclusion, we propose this model as a useful tool to study adipose inflammation in vitro. It represents an inexpensive, highly reproducible human system. The methods described here can be easily extended for usage of primary human macrophages and fat cells.